Guerra cristera y orden público en Coalcomán, Michoacán, 1927-1932 - Guerra Manzo, Enrique (El Colegio de México, A.C., 2001)
This work studies the  development of the Cristero Rebellion (1927-1929) in Coalcoman County (southwestern Michoacán), and the problems of reestablishing public order between 1929 and 1932. The main argument is that the strength of Catholicism in this region, expressed in the resistance of the Cristeros of Coalcoman towards the attacks of the federal army, forced the reconstruction of the new public order to take them into account. At the end of the rebellion, when the local agrarist faction became uncapable of establishing peace, the government had to accept some members of the Catholic faction, former Cristero leaders, as civil authorities, and this implied sacrificing part of the postrevolutionary State's religious policy.